A new HLA‐B allele, HLA‐B*07:422. (10th November 2021) - Battarra, Mariarosa; Di Luzio, Andrea; Bianculli, Antonio Giuseppe; Pinto, Rita Maria; Andreani, Marco
Abstract : The novel allele HLA‐B*07:422 differs from HLA‐B*07:02:01:01 by one nucleotide substitution in exon 4.